Large Accumulation of Collagen and Increased Activation of Mast Cells in Hearts of Mice with Hyperlipidemia - Yunpeng Cheng; Yanqiu Zhu; Jiashu Zhang; Xingping Duan; Ying Zhang (Arquivos Brasileiros de Cardiologia, 2017)
Abstract Background: Hyperlipidemia, which is characterized by an elevation of lipids in the bloodstream, is a major risk factor for cardiac disease. Objectives: The present study investigated the role of fibrosis in the progression of hyperlipidemia in the mice heart, and whether mast cell activation was associated with the fibrosis process. Methods: Hyperlipidemia was produced in C57BL / 6 mice by feeding them on a high-fat diet for 8 weeks.To assess tissue fibrosis, picrosirius red staining was performed. Hematoxylin & eosin (H&E) staining was performed to identify the histopathological changes in the hearts. Immunohistochemistry was also accomplished to determine the localization of transforming growth factor (TGF)-β and α-smooth muscle actin (α-SMA). Western blotting was performed to analyze the expression of chymase, tryptase, TGF-β, α-SMA and activity of Wnt/β-catenin pathway. At the end, serum total cholesterol (TC) and triglycerides (TG) levels were measured. All the values were expressed as means ± SD, the statistical significance level adopted was 5%. Results: Hyperlipidemia mice showed significantly increased collagen deposition in the hearts compared with normal mice. In addition, H&E staining showed significant cellular degeneration. Cardiac muscle was arranged in disorder with fracture in mice of the model group. Immunohistochemistry and western blot analysis revealed that expression levels of tryptase, chymase, β-catenin, TGF-β and α-SMA were significantly increased in the hyperlipidemia mice compared with the control group. Conclusions: The results indicated that mast cell activation might induce cardiac fibrosis by tryptase and chymase in hyperlipidemia, which had a close relationship with the increased activity of TGF-β/Wnt/β-catenin pathway.